Rationalistic Sects of Doukhobors and Molokans in Tobolsk Province in 19th — Early 20th Centuries: Distribution, Numerical Composition, and Religious Culture - E. V. Kostetskaya; L. N. Suslova; K. E. Zolnikova (Научный диалог, 2024)
This article focuses on studying the peculiarities of the beliefs, religious cults of Doukhobors and Molokans, the specifics of community formation of these rationalistic sects, and the numerical composition of their religious followers in the territory of Tobolsk Province. Materials from the Tobolsk State Archive, the newspaper “Tobolskie Eparkhialnye Vedomosti,” as well as works of pre-revolutionary, Soviet, and contemporary researchers were utilized. Among the rationalistic sects, Doukhobors, Molokans, and Nemolyaks (sectarians who don’t pray) were identified as the main religious movements of sectarians in the studied territory. The article analyzes the formation of religious communities, the residential areas of sectarians of different denominations in Tobolsk Province, the peculiarities of their self-organization, and the functioning of sects. It is noted that people joined these sects seeking to understand the Bible and searching for a just social order, placing them in opposition to the official church and state. The social base of rationalistic sects consisted of peasants and townspeople (burgher class). Statistical analysis showed a slight increase in the number of sectarians in Tobolsk Province during the second half of the 19th century and a significant surge in the early 20th century. From 1855 to 1913, the number of sectarians increased from 182 individuals to 1473 individuals.